The affect of some natural preservative solutions and immersion time on the quality of chrysanthemum cut flowers (Chrysantemum morifolium L.) - RITA HAYATI; RIFA NARIZKY; AINUN MARLIAH (Jurnal Natural, 2022)
Chrysanthemum morifolium L. is one of the ornamental plants that has problems in maintaining the freshness of the flower. The handling given to maintain the shelf life of the flower is to soak the flowers with a natural preservative solution. This study aims to find out the effect of several types of natural preservative solutions and long soaking on the quality of freshness of chrysanthemum cut flowers, as well as to find out whether there is an interaction between the two treatments. This research was conducted at the Laboratory of Seed Science and Technology and Horticulture Laboratory of the Department of Agrotechnology, Faculty of Agriculture, University of Syiah Kuala, Banda Aceh from March 30 to April 15, 2021. The study used a Complete Randomized Design of a 4 x 3 Factorial pattern with 3 repeats. The parameters observed include the diameter of the full blooming flower, the flower's ness index, the flower freshness period index, total absorbed solution, color measurement and organoleptic test. The results showed that the combination of treatment between natural and long-soaked solution types had a real effect on the parameters of the flower freshness index. The best freshness period of flowers is in the combination of 10% sugar solution type treatment with a 6-hour soaking length.